2021
DOI: 10.7759/cureus.14185
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral Sternalis With Double Slips: An Astounding Muscle, Often Unnoticed and Unknown

Abstract: Discovery and variations of rectus sternalis muscle are occasionally seen in humans. However, during routine academic dissection of an adult male embalmed cadaver, a rare variant of the muscle was identified. The muscle had origin from the pectoral muscle and fascia and was inserted into external oblique aponeurosis along with the sixth rib and cartilage. It had double slips with the partial merging of the bellies. Knowledge regarding such unique muscle is important to anatomists for medical education as well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…It has been reported that the muscle is derived from neighbouring muscles like Sternocleidomastoid (SCM), Pectoralis major, Rectus abdominis. The present muscle fibres could be a variant of Pectoralis major as can be interpreted from its attachments along the sternum and External oblique aponeurosis (7). The muscle is commonly reported to be present unilaterally but if it occurs bilaterally, it is usually asymmetric with the right side better developed than the left one (10).…”
Section: Discussionmentioning
confidence: 90%
“…It has been reported that the muscle is derived from neighbouring muscles like Sternocleidomastoid (SCM), Pectoralis major, Rectus abdominis. The present muscle fibres could be a variant of Pectoralis major as can be interpreted from its attachments along the sternum and External oblique aponeurosis (7). The muscle is commonly reported to be present unilaterally but if it occurs bilaterally, it is usually asymmetric with the right side better developed than the left one (10).…”
Section: Discussionmentioning
confidence: 90%